Sosialisasi Masyarakat Remaja Melawan Narkoba di Panti Asuhan Dharma Laksana - Kadek Ananta Husada Arsa; Puji Arrohman; Niti Wedayani AAA; Novia Andansari (Universitas Mataram, 2022)
Drug abuse affects almost all levels, especially the younger generation. Children and adolescents are the nation's next generation that must be protected from drug abuse, because drugs have a major impact on health, economy, and socio-culture, and even the destruction of a nation. Drugs can cause physical and psychological dependence. According to President Joko Widodo, the situation in this country is in a Drug Emergency Status. Narcotics are substances or drugs made from natural, synthetic, or semi-synthetic materials that can cause a decrease in consciousness according to Law No. 35 of 2009 concerning Narcotics Article 1 paragraph 1. The negative impact of the use of Narcotics in addition to causing health impacts in the form of dependence, lowering the level of awareness even to the point of death. Circulation and use of drugs is no longer limited to social class and geographical location. This is very concerning, especially if those who become drug users are the younger generation, especially students who will become the nation's next generation. Therefore, the participation of all parties, both in the fields of law and health, in disseminating information about the dangers of drug use is very important. Survey and Education. The survey was conducted to select and determine the location for the implementation of service activities. Education is provided by providing counseling to the children of the Dharma Laksana orphanage. The legal counseling in the form of providing education was attended by the chairman of the orphanage, administrators of the orphanage, several lecturers and doctors of the medical faculty of the University of Mataram. Material counseling was given by Kadek Ananta Husada, S.H. After the counseling, health checks were carried out by lecturers and doctors of the Faculty of Medicine, University of Mataram. The number of children in the orphanage is 46 students consisting of SD-SMP-SMA. And 10 Foundation Management and Orphanage teaching staff.